EVALUATING THE EFFECTIVENESS OF BANKING SECTOR CREDIT IN PROMOTING INVESTMENT AND GROWTH IN NIGERIA'S REAL SECTOR - Ahmed , H; G, Jayaraman; Ahmed , H (Economics and Statistics Research Journal (ESRJ), 2022)
This study analyzes the impact of banking sector credit on Nigeria's real sector using data from 1986 to 2019. The study employs the ARDL model to examine the relationship between commercial bank credit, domestic private investment, government capital expenditure, and real gross domestic product (RGDP). The findings show a positive impact of commercial bank credit on RGDP in both the short and long runs. However, the study reveals a negative and significant association between domestic private investment and RGDP in both the short and long runs. In addition, the study emphasizes the crucial role of government capital expenditure in promoting economic growth, with a significant positive relationship identified between GCE and RGDP. The study concludes that effective utilization and distribution of bank credit can significantly enhance output, thus promoting economic growth. Therefore, the study recommends the need for improved banking sector credit to increase the output of the real sector, which will, in turn, boost economic growth in Nigeria. The article contributes to the existing literature by illustrating the favorable and significant connection between commercial bank credit and RGDP in Nigeria